Walking Distance to Tobacco Outlets in Vulnerable Areas Baltimore City: An Issue of Health Equity - Aruna Chandran; Christian Fuller; Emilie Gilde (Archives of Community Medicine and Public Health - Peertechz Publications, 2017)
Introduction: Health equity concerns related to tobacco use are signifi cant in Baltimore City. We use spatial analytic techniques to understand the density of tobacco outlets by areas of socioeconomic vulnerability, and their location within walking distance of residences compared with vehicle ownership. Methods: Population demographic indicators were obtained from the 2010 Census and associated with increasing numbers of tobacco outlets using a linear regression model. The distance from the  centroid of each census block to the nearest licensed tobacco retailer was calculated using a spatial joining techniques. Results: In Baltimore City, there are 3.18 tobacco retailers per 1,000 residents ages 16 and over. Indicators of vulnerability associated with increased numbers of tobacco retailers include lower median household income (p=0.006), lower employment (p=0.045), increased poverty (p=0.009), and increased density of Class A liquor outlets (p<0.001). The proportion of households per census tract that don't have access to a vehicle is signifi cantly associated with increased number of tobacco retailers (p=0.003); 85% of census tracts have an average distance of ¼ mile or less to the nearest tobacco vendor. Conclusions: Tobacco retailers in Baltimore are located in areas of highest neighborhood deprivation. Importantly, our analysis shows a powerful correlation between those areas lacking vehicle ownership with the highest number of tobacco vendors; those individuals that rely on walking or public transportation are the ones with tobacco retailers within a ¼ mile walking distance. One policy option is linking zoning restricting tobacco retailers from vulnerable neighborhoods in order to promote health and health equity.